Аналіз причин появи додаткових похибок вимірювання витрати природного газу, зумовлених змінами параметрів нестаціонарного потоку - Федоришин, Роман; Грень, Ярослав; Матіко, Федір (Видавництво Національного університету «Львівська політехніка», 2009)
This paper deals with influence of non-stationery flow parameters variations on the results of natural gas flow rate and volume measurement by means of standard pressure differential devices. Results of investigation of such an influence are given. The additional errors of natural gas accounting caused by non-stationery and pulsating regime of flow at measuring section of the pipeline are revealed. The existing approaches to defining and eliminating the influence of non-stationery flow parameters variations on the results of natural gas flow rate and volume measurement are analysed.
Keywords: flow rate; measurement; natural gas; pressure differential device; non-stationery regime; flow pulsations; additional errors